The potential for medical tourism in Halabja Governorate - مارف, شه ماڵ علی (Sulaimani Journal for Humanities, 2019)
Therapeutic tourism has played major role all over the world in recent years as means of getting hard currency and to support countries’ economies and development. Thus, The countries that have Therapeutic sources started to invest Them Through spas , where sulphurous springs and various kind of sand and alluvial mud that help people recover from rheumatic and skin diseases and such other ailments . 165 مجلة )زانکۆی سلێمانی( القسم )B)للدراسات اإلنسانیة – العدد )95( کانون الثاني 1025 There are numerous places in study area That are suitable for the establishment of Therapeutic tourism centers Therein , but as such locations are not properly invested ( and even The planning for their development has not yet been started ) resulted in keeping such places unutilized . As a matter of fact, most Kurdish people do not know any other Therapeutic spas except mineral water spring (garawaka) “in khurmal though there are many other places in halabja governorate are fit to serve this purpose. All these advantages are to the interest of establishing Therapeutic sites and spas. Some of these sites have particular importance which will definitely attract large numbers of tourists. Despite the fact that the water of Garaw spring is not suitable for drinking nor irrigation , as it is highly saline , yet such water could be utilized for Therapeutic purposes and this was ascertained by numerous studies conducted on the chemical , physical and biological characteristics of such springs prior to using their water for therapy and cure . In addition to the possibilities that study area possesses in order to establish Therapeutic tourism industry therein, field studies revealed that human resources also support setting up such a type of tourism. The local population encourage starting this aspect of development in their area. This will also result in the availability of work opportunities in the new facilities. All these resources, combined, plus social harmony, wait the proper planning in order to develop this area in terms of therapeutic tourism.